Возрастные особенности реакции сердечно-сосудистой системы юных пловцов на дозированную физическую нагрузку - Юшко, Алексей Владимирович; Баламутова, Н. М.; Блошенко, Елена Ивановна; Шейко, Л. В. (Національний педагогічний університет ім. М. П. Драгоманова, 2020)
В возрастной педагогике и физиологии одним из важных вопросов является изучение влияния физических нагрузок на состояние сердечно-сосудистой системы детей и подростков. Реакции сердечно-сосудистой системы в ответ на физическую нагрузку имеют существенные возрастные и половые различия. В связи с этим анализировались показатели сердечно-сосудистой системы при работе на велоэргометре у школьников до начала, в период и к моменту завершения полового созревания. Целью данного исследования явилось изучение возрастных особенностей реакции сердечно-сосудистой системы испытуемых на дозированную физическую нагрузку. Выявленные закономерности реакции сердечно-сосудистой системы детей школьного возраста на физическую нагрузку могут служить критерием для оценки их функциональных возможностей.

In the age-related pedagogy and physiology one of important questions is the study of the influence of physical activities on the state of the cardiovascular system of children and teenagers. The reactions of the cardiovascular system in response to physical activity have significant age and gender differences. In this regard, the indicators of the cardiovascular system were analyzed when working on a bicycle ergometer in schoolchildren before, during, at the time of completion of puberty. The aim of this research was to study the age-related characteristics of the testes' cardiovascular system response to dosed physical activity. The revealed regularities of the reaction of the cardiovascular system of school-age children to physical activity can serve as a criterion for assessing their functional possibilities.
Age-related characteristics of the reaction of the cardiovascular system of young swimmers to dosed physical activity
Keywords: дети; подростки; половое созревание; время восстановления; дисрегуляторная реакция; дозирование нагрузки; children; teenagers; physical activity; cardiovascular system